PENERAPAN STRATEGI PBAS (PEMBELAJARAN BERORIENTASI AKTIVITAS SISWA) DALAM MENINGKATKAN HASIL BELAJAR - Tita Junita; Fitri Oviyanti; Sukirman Sukirman (PAI RAFAH, 2022)
The research was conducted to see hoe to implementation of the PBAS (Student Activity Oriented Learning) strategy of MA Al-Fatah Palembang. Anda also to see how student learning outcomes in the experimental class and control class.The type of research used here is experimental research with the Posstest – Only Control Design design.this research uses a quantitative approach. Furthermore, in the research the data method used was the method of observation, tests, and documentation.The learning outcomes that are carried out, the implementation of the PBAS (Student Activity Oriented Learning) strategy is carried out in the tages of planning, implementation, and evaluation.The result showed that the student learning outcomes of the experimental class were higher than the control class, with the result of the t test hypotesis: (t0 =6,142) and the size shown in the t value table (ttabel 5%=2,02 dan ttabel 1%= 2,71) accepted, the proposed acceptance is 2,02<6,124>2,71, and the null hypotesis is rejected. This means that the increase in learning outcomes after implementing the PBAS (Student Activity Oriented Learning). Strategy.